WordPress Top Plugins. - Corbin, Brandon (Packt Pub., 2010)
Time flies when you're having fun. This is the right way to describe this WordPress Top Plugins book by Brandon Corbin. With real world examples and by showing you the perks of having these plugins installed on your websites, the author is all set to captivate your interest from start to end. Regardless of whether this is your first time working with WordPress, or you?re a seasoned WordPress coding ninja, WordPress Top Plugins will walk you through finding and installing the best plugins for generating and sharing content, building communities and reader base, and generating real advertising r.